2022
DOI: 10.3390/polym14061123
|View full text |Cite
|
Sign up to set email alerts
|

Linearization of Composite Material Damage Model Results and Its Impact on the Subsequent Stress–Strain Analysis

Abstract: To solve problems in the field of mechanical engineering efficiently, individual numerical procedures must be developed, and solvers must be adapted. This study applies the results of a carbon-fibre reinforced polymer (CFRP) analysis along with the nonlinear finite element damage (FE) method to the translation of a linear solver. The analyzed tensile test sample is modelled using the ply-by-ply method. To describe the nonlinear post-damage behavior of the material, the Hashin model is used. To validate the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…After simulating the impact with material failure [28][29][30][31][32][33], the task was linearized, and the results were reformulated for the Abaqus/Standard solver. Linearization was performed using the procedure detailed in [34,35]. Its purpose is to replace several damage modes with a single material card.…”
Section: Post-impact Simulation Testmentioning
confidence: 99%
“…After simulating the impact with material failure [28][29][30][31][32][33], the task was linearized, and the results were reformulated for the Abaqus/Standard solver. Linearization was performed using the procedure detailed in [34,35]. Its purpose is to replace several damage modes with a single material card.…”
Section: Post-impact Simulation Testmentioning
confidence: 99%
“…The results exhibit that the composite has good puncture resistance, the interlayer structure dissipates puncture energy to a certain extent, and the LMPET layer avoids the sliding of the filament during the needle punching process, thus improving the overall mechanical properties of the laminated composite. Due to excellent high strength and high modulus, carbon fiber (Samal et al ., 2016a, b; Samal, 2022; Vlach et al ., 2022a, b) is also widely used as an interlayer reinforcement to enhance the mechanical properties of composites. Another way is to enhance the static puncture resistance of materials by structural design and optimization.…”
Section: Introductionmentioning
confidence: 99%
“…The delamination propagation path first extends along the width direction to the center, and then along the length direction [ 25 , 26 ]. Further research showed that the damage is layer-dependent in a laminate, and different fiber materials influence the delamination resistance in different ways [ 27 , 28 , 29 ]. The closer the delamination is to the surface, the lower the bearing capacity of the specimen, and the easier it is for interface cracking, interlaminar cracking, and fiber fracture to occur.…”
Section: Introductionmentioning
confidence: 99%